Short Communication: Evaluation of quantitative and qualitative morphological characters of sunflower (Helianthus annuus) germplasm - RULLY DYAH PURWATI; ANIK HERWATI (Biodiversitas Journal of Biological Diversity, 2016)
Purwati RD, Herwati A. 2016. Evaluation of quantitative and qualitative morphological characters of sunflower (Helianthus annuus) germplasm. Biodiversitas 17: 461-465. Sunflower (Helianthus annuus L.) germplasm collection in ISFCRI was characterized aiming to distinguish the morphological characters of each genotype. Based on that information it would be possible to observe the diversity and to choose appropriate parent genotypes for successful hybridization. The investigation was carried out in the Pasirian Experimental Station, Lumajang District, East Java, Indonesia located at 110 m above the sea level (113° E, 8° S) in the 2015 growing season. Thirty-three germplasm accessions were characterized. Each accession was planted in 32 m² plot size with four lines. Fertilizer dose was 75 kg Nitrogen + 30 kg P2O5 + 30 kg K2O per ha. The results showed that the low variation value in some quantitative characters such as seed size, weight of 100 seeds, seeds thickness, plant height, leaf size, ray floret length, bract length, head diameter, the flowering time, and seed oil content. The qualitative characters exhibited high coefficient of variation values with only one exception-pollen formation in sunflower inflorescences. These results indicated that on the base of their qualitative morphological characters, sunflower accessions possessed high diversity. The seed size and seed thickness showed significant positive correlation with 100 seeds weight. These two characters might be used as selection criteria in sunflower breeding programs for appropriate screening of parental genotypes included in hybridizing process aiming the increase of plant productivity.